2015
DOI: 10.1118/1.4903262
|View full text |Cite
|
Sign up to set email alerts
|

Comparing nonrigid registration techniques for motion corrected MR prostate diffusion imaging

Abstract: The authors' results show that the "fast elastic image registration" provides most accurate results with a target registration error of 1.07 ± 0.41 mm at minimum execution times of 11 ± 1 s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…From the tumor segmentation, the whole tumor volume and the enhancing portion of tumor volume (cm 3 ) could be obtained. To measure the enhancing volume, the CT scan obtained just before contrast medium administration (i.e., unenhanced CT scan) was registered to the arterial phase CT scan and then subtracted in order to remove any background attenuation [5, 15]. The subtraction is a key feature because it mitigates contribution of background attenuation from the Lipiodol deposition that would otherwise obscure the true enhancement from the contrast medium injection (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…From the tumor segmentation, the whole tumor volume and the enhancing portion of tumor volume (cm 3 ) could be obtained. To measure the enhancing volume, the CT scan obtained just before contrast medium administration (i.e., unenhanced CT scan) was registered to the arterial phase CT scan and then subtracted in order to remove any background attenuation [5, 15]. The subtraction is a key feature because it mitigates contribution of background attenuation from the Lipiodol deposition that would otherwise obscure the true enhancement from the contrast medium injection (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Crum et al found FFD B‐spline methods utilizing the NMI metric superior to affine registration using the correlation ratio metric and fluid modeling methods utilizing the CC metric, when propagating segmentations of brain regions on MR. Hawkins, Wittek, and Miller contrasted the use of a hyperviscoelastic material, a hyperelastic model and an elastic model for modeling brain deformations, finding no significant performance variation between the models. Buerger et al performed an evaluation of FFD B‐spline registration (with a gradient descent and a Levenberg–Marquardt optimizer), HALA registration, Demons registration and elastic model registration for motion correction in prostate MR imaging. The elastic model was found to provide superior accuracy and computation time.…”
Section: Technologies and Techniquesmentioning
confidence: 99%
“…Specifically, several studies have compared registration techniques for various MRI sequences in the prostate[31][32][33]. For example, Buerger et al compared the performance of five state-of-the-art DIR image registration techniques for accurate image fusion of DWI with T2W images and found fast elastic image registration provided improved performance compared to other deformable techniques such as B-spline and Demons[32]. This result was further echoed in Eriksson et al, which confirmed that fast elastic image registration was the best technique for T1-weighted to T2W anatomic sequence registration[33].…”
mentioning
confidence: 99%
“…However, intra-acquisition MRI registration techniques have been investigated in other anatomical sites. Specifically, several studies have compared registration techniques for various MRI sequences in the prostate[31][32][33]. For example, Buerger et al compared the performance of five state-of-the-art DIR image registration techniques for accurate image fusion of DWI with T2W images and found fast elastic image registration provided improved performance compared to other deformable techniques such as B-spline and Demons[32].…”
mentioning
confidence: 99%